Large Cumulative Capacity Enabled by Regulating Lithium Plating with Metal–Organic Framework Layers on Porous Carbon Nanotube Scaffolds. (6th August 2021) - Noh, Juran; Chen, Wenmiao; Wu, Peng; Huang, Yutao; Tan, Jian; Zhou, Hong‐Cai; Yu, Choongho
Abstract: The high specific capacity of lithium metal is ideal to meet the current demand in rechargeable batteries but lithium dendrites and irreversible volume expansions are major hurdles. 3D lithium host materials can alleviate these problems by lowering the current density with large surface areas and accommodating lithium metal in their pores. However, lithium dendrites are persistently observed because of sluggish lithium‐ion diffusion through tortuous pores, resulting in clogging and thereby dendrite growth. Herein, layered metal–organic frameworks (MOFs) are deposited on carboxylated carbon nanotube (CNT) scaffolds via coordination bonding. The MOF layer on the outside of the CNT scaffold has augmented lithium insertion into the porous scaffolds (24 mAh cm −2 at 8 mA cm −2 ) and lithium plating/stripping lifetime (over 1700 h with 20 mAh cm −2 cycle −1 ). MOF has pores large enough for lithium ions to permeate through, and its electronically insulating property creates capacitive effects, distributing lithium ions over the surface of the MOF layer to avoid dendrite growth and clogging during lithium plating. Outstanding volumetric and gravimetric capacities (≈940 mAh cm −3 and ≈980 mAh g −1 ) along with exceptional cumulative capacity (≈4.9 Ah cm −2 ) are obtained. This promising approach can store lithium without dendrites to deliver high energy densities required for the current rechargeable batteries. Abstract : The electronically insulating metal–organic framework coated on the carbon nanotube (CNT) scaffolds prevents lithium dendrite growth while the lithiophilic surface of the CNT in the inner pores attracts lithium ions for storing lithium metal, providing a large cumulative capacity of ≈4.8 Ah cm −2 cycle −1 at an areal capacity of ≈20 mAh cm −2 .